Pelindungan Hukum Korban Tindak Pidana Pencucian Uang Terhadap Permohonan Penetapan Sita Eksekusi - Mahendro, Guntar; Nugraheni, Destri Budi (Officium Notarium, 2025)
This study aims to analyze the legal protection for victims of money laundering against the rejection of resistance to the execution of mortgage rights. The analysis was conducted against the background of the verdict of the Cibinong District Court Number 582/Pid.B/2019/PN.Cbi which ruled that one of the results of the money laundering crime in the form of SHGB No. 5993 was returned to the victim but the object of dispute was in the process of execution of a mortgage. This type of research is normative legal research. Normative research is legal research conducted by examining library materials or secondary data. The data in this research is secondary data obtained through literature study and supported by primary data obtained by interviewing sources. The data obtained in this study were analyzed using qualitative methods and then presented descriptively. The results of this study show that the creditor holding the Mortgage Rights has a separatist right guaranteed by the Mortgage Rights Act must take precedence over other creditors. Legal protection for victims of money laundering crimes against the rejection of resistance to the execution of mortgage rights is that they can file a new civil lawsuit to the district court to sue the object of the dispute by adding a new defendant so that it is not Nebis In Idem. In addition, it can be attempted in good faith to mediate between the defendant and the victim for the loss incurred. Victims of money laundering crimes can file extraordinary legal remedies, namely by reviewing the decision of the third party resistance (derden verzet). Seeking good faith towards the victim through mediation related to material damages.